Towards a consolidated database of distortions agricultural incentives: the Ag-Incentives Consortium - Tokgoz, Simla; Laborde Debucquet, David; Majeed, Fahd; Lallemant, Tess (2017)
It is important to measure and analyse the impacts of policy design on agricultural markets. Indirect measurement of incidence, e.g. nominal rate of protection (NRP), is one reliable method to do this, as it relies on price gaps between what producers see and what is prevailing in international markets. Ag-Incentives Consortium, a collaboration effort among international organizations that work on measuring distortions to agricultural incentives, is a new initiative that attempts to bring clarification, harmonization, and methodological guidelines to the forefront. This study, based on but not limited to Ag-Incentives, computes NRPs based on a combined input data from all IOs. The results show that high income countries have decreased protection over time, whereas middle income countries have increased it. Low income countries have higher variation in protection, and respond to food price crises of 2008 and 2011 differently from high and middle income countries.